2017
DOI: 10.1387/revpsicodidact.15501
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personal Characteristics and School Characteristics in Explaining Teacher Job Satisfaction

Abstract: a b s t r a c tRecent studies show that teacher job satisfaction declined in Spain over the last decade. Also, it is significantly lower in secondary education than in previous educational levels. In this paper we identify variables that contribute to the explanation of teacher job satisfaction in secondary education. We use the Spanish sample (192 schools and 3339 teachers) participating in the 2013 edition of TALIS (Teaching and Learning International Study), sponsored by the OECD (Organisation for Economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
0
19
0
5
Order By: Relevance
“…Finally, the three multi-group CFA present the EME-ES as a partially invariant (i.e., configural and metric) instrument in different samples of teachers, by gender and type of school. These findings are highlighted because of the influence that gender and type of school could have on teachers’ motivation and other work outcomes (Fernet et al, 2008; Gil-Flores, 2016; Nie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the three multi-group CFA present the EME-ES as a partially invariant (i.e., configural and metric) instrument in different samples of teachers, by gender and type of school. These findings are highlighted because of the influence that gender and type of school could have on teachers’ motivation and other work outcomes (Fernet et al, 2008; Gil-Flores, 2016; Nie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, past studies have shown that female teachers present higher levels of intrinsic motivation and identified regulation, and lower levels of introjected and external regulation and amotivation toward teaching than their male counterparts (Fernet et al, 2008; Nie, Chua, Yeung, Ryan, & Chan, 2015). Several studies have also suggested that the type of school could affect teachers’ work motivation processes, particularly in Spain (Gil-Flores, 2016; Latorre & Saéz, 2009). For example, Latorre & Sáez (2009) showed that teachers in state schools reported less motivation than teachers in non-state schools.…”
Section: Objective and Hypothesismentioning
confidence: 99%
“…Por su parte Spector (1985), en su momento, conceptualizó esta variable como el conjunto de beneficios cualitativos y cuantitativos, que los empleados perciben recibir de su organización a cambio de trabajo y esfuerzo, y en donde, en consecuencia, se genera un estado emocional que beneficia el compromiso, agrado y responsabilidad de su desempeño individual ( de sentimientos que influyen de manera importante en su bienestar y compromiso laboral (Chiang, Gómez e Hidalgo, 2017). Normalmente la SL se relaciona con otras variables como el bienestar del empleado (Hosie, Sevastos y Cooper, 2007), la rotación laboral, el ausentismo, el compromiso organizacional, la motivación y otras emociones y conductas de los trabajadores (Cernas et al, 2018;Chiang et al, 2008;Gil, 2017).…”
Section: Capital Humano Y Su Relación Con El Desempeño Organizacional: Revisión De Literaturaunclassified
“…This could represent a theoretical and methodological advance in the development of the scale to evaluate teachers' perception of their interpersonal styles (i.e., NSTSS), because in the initial validation of student perception of teachers' interpersonal styles (i.e., MCPES;Soini et al, 2014), measurement invariance was not examined. Furthermore, these findings must be highlighted because of the influence that both gender and type of school may have on the development of teachers' motivational processes and, therefore, on their interpersonal teaching styles (Gil-Flores, 2016;Latorre & Sáez, 2009;Reeve et al, 2014). Importantly, if we want to examine teachers' interpersonal styles to evaluate their influence on their motivation to teach, the first step is to do it with invariant scales across teacher gender and type of school, such as the NSTSS.…”
Section: Measurement Invariance Of the Nstss (Hypohesis 2)mentioning
confidence: 99%